Tessituras da cultura corporal em uma escola indígena do alto rio Negro no Estado do Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
This study had the following general objective: to analyze how the Corporal Culture shows itself in physical education classes of the indigenous school of elementary school and in everyday community, community - Camanaus Duraka Island/ São Gabriel da Cachoeira/ Amazon. The specific objectives were to analyze the Body Culture in Physical Education classes and to describe how cultural influences manifest occur in the (re) creation of community sports in Island Duraka - Camanaus . Aspects were analyzed daily to do with the body in the way of everyday life of Indigenous Peoples: hunting, fishing, planting and harvesting, the dancing, the making of flour, crafts, body paintings, myths and stories daily, the games, educational activities, weaving a relationship with the Body Culture practiced in regular classes Municipal School Indigenous Marechal Dutra, especially in physical education classes. The theoretical approach was used Geertz (1989) and Malinowski (1975), Laraia (2011) and Weigel (2000), the approaches to culture; Mauss (2003), Daolio (2005) , Soares (2010), Grando (2005, 2010) , Vinha (1999, 2005) Rocha Ferreira (1999, 2005) and Fassheber (2006 ), issues related to Body Culture in diverse contexts. It is a research field that can also be characterized as non- interventional observational , with a qualitative descriptive approach. For data collection we used the field notebook and semi-structured interviews, attended twenty five indigenous people of the community, these being: Indian teachers, Indian parents and Indian leaders. It was important to (re) discover, by the indigenous community, the forms of pedagogical applicability of cultural meanings of body activities - games, plays, dances, parties, short of bodily practices as a way to enhance and encourage the preservation of millennial wisdom of Culture body of Indigenous Peoples .
Keywords: Cultura Corporal; Cultura Indígena; Etnodesporto e Lazer; Educação Escolar Indígena; Indígenas do Alto Rio Negro; Body Culture; Indigenous Culture; Sport and Recreation; Indigenous Education; Indigenous Upper Rio Negro; CIÊNCIAS HUMANAS: EDUCAÇÃO